SYNTHESIS AND ANTICANCER SCREENING OF TRIAZINE ANALOGUES - Tiwari, Anshuly; Modi, Siddharth J.; MAHADIK, KAKASAHEB R; Suryawanshi, Mugdha R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The study was aimed to investigate the cytotoxic effect of S-5H-[1,2,4]-triazino (5,6-b) indol-3-yl-3,4-phenylethane-thioate derivatives as epidermal growth factor Receptor (EGFR) inhibitors. Methods: In the present study 14 novel triazine analogues were synthesized and characterized using different spectroscopic techniques such as FT-IR, NMR and Mass Spectroscopy. The anticancer activity was performed using MCF-7 (breast cancer) and K-562 (leukaemia) cell lines. Further, molecular docking was carried out using Vlife Molecular Docking Software (MDS) on crystal structure of epidermal growth factor receptor (EGFR) to identify the binding mode of interaction with an active site. Results: Compounds MA-7, MA-8, MA-12, MA-13 and MA-14 show potent activity against cancer cell lines in the range of<10 to 84.4 µg/ml. Further molecular docking on EGFR also supports that there is a strong correlation between in silico and in vitro biological activity. The results of this study may be further useful for lead optimization process. Conclusion: The results of this study indicates that the synthesized triazine analogues can give a potential lead as an anticancer agent.